2020
DOI: 10.1111/ors.12473
|View full text |Cite
|
Sign up to set email alerts
|

Temporomandibular disorders: a review of current concepts in aetiology, diagnosis and management

Abstract: Temporomandibular disorders (TMD) is a collective term for a group of musculoskeletal conditions involving pain and/or dysfunction in the masticatory muscles, temporomandibular joints (TMJ) and associated structures. It is the most common type of non-odontogenic orofacial pain and patients can present with pain affecting the face/head, TMJ and/or teeth, limitations in jaw movement and sounds in the TMJ during jaw movements. Comorbid painful and non-painful conditions are also common among individuals with TMD.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
60
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(76 citation statements)
references
References 83 publications
1
60
0
2
Order By: Relevance
“…Temporomandibular disorders (TMDs) are a heterogeneous group of musculoskeletal conditions typified by pain and/or dysfunction of the stomatognathic system. 1 Based on physical examination/self-reported surveys, up to 75% of people have signs and/ or symptoms of TMDs. 2 The prevalence of TMDs ranges from 6% to 16% when determined using formalised diagnostic criteria.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Temporomandibular disorders (TMDs) are a heterogeneous group of musculoskeletal conditions typified by pain and/or dysfunction of the stomatognathic system. 1 Based on physical examination/self-reported surveys, up to 75% of people have signs and/ or symptoms of TMDs. 2 The prevalence of TMDs ranges from 6% to 16% when determined using formalised diagnostic criteria.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Conservative “reversible” management of TMD remains the most common approach to the management of more than 90% of patients [ 9 ]. Conservative treatment methods for TMDs include psychological [ 10 , 11 ], splints [ 9 , 12 ], pharmacological therapies [ 13 , 14 ], physiotherapy [ 15 , 16 ], self-management [ 17 ], and low-level laser therapy (LLLT) [ 18 , 19 , 20 ]. Irreversible treatment involves orthodontics, occlusal adjustments [ 21 , 22 ], and surgery [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…While some studies investigating the role of TMJ disorders and occlusal factors found a positive relationship between signs and symptoms of TMJ diseases and Angle classi cation and occlusal guidance factors, no relationship was found in some studies. However, with the thought that malocclusion is the most important factor leading to TMJ disorders, irreversible occlusal adjustments are made by dentists today as in the past [13]. The aim of this study is to determine the distribution of occlusal factors and whether there are changes in the joint due to this in individuals receiving xed orthodontic treatment.…”
Section: Introductionmentioning
confidence: 99%